Use of the CLARKE JU6H-NL30 Diesel Pump in Building Fire Suppression Systems: Penggunaan Pompa Diesel CLARKE JU6H-NL30 Pada Sistem Pemadam Kebakaran Gedung - Rahmadin, Mohamad Affan; Iswanto , Iswanto (Procedia of Engineering and Life Science, 2024)
This study investigates the suitability of the Clarke JU6H-30NL diesel pump engine as a supplementary solution for fire extinguishing systems in a banking facility during August–September 2023. Employing practical fieldwork methods, we analyzed the specifications, operational procedures, and benefits versus drawbacks of diesel pumps compared to electrical alternatives. Observational techniques were utilized to collect real-time data onsite. Our findings reveal that diesel pumps offer significant advantages such as uninterrupted operation during power failures, elevated water pressures, lower maintenance costs due to more accessible spare parts, and enhanced overall building safety and resilience against fires. These insights suggest that incorporating diesel pumps into existing fire protection strategies could provide reliable backup solutions, particularly in critical infrastructure settings where continuous operations are crucial. highlight: The study analyzed the specifications, operational procedures, and benefits versus drawbacks of diesel pumps compared to electrical alternatives. Observational techniques were utilized to collect real-time data onsite. Diesel pumps offer significant advantages such as uninterrupted operation during power failures, elevated water pressures, and lower maintenance costs due to more accessible spare parts. Keywords: Clarke JU6H-30NL diesel pump engine, fire extinguishing systems, banking facility, uninterrupted operation, building safety.